Journalism, media, and technology trends and predictions 2025 - Newman, N; Cherubini, F (Reuters Institute for the Study of Journalism, 2025)
This annual Reuters Institute Predictions report looks at the key trends that will impact news media in 2025. Just four in ten (41%) of our sample of editors, CEOs, and digital executives say they are confident about the prospects for journalism in the year ahead. Stated concerns relate to political polarisation, a rise in attacks on the press, and media capture. The report also shows different ways in which publishers are adopting generative AI. Beyond more efficient workflows, publishers will be working on audience-facing features such as turning text into audio and providing automated story summaries and translations. Publishers are also worried about a significant fall in referrals from search as big tech companies integrate AI overviews and other ‘story-like’ responses to news queries. There will be more focus this year on video platforms such as YouTube, TikTok and Instagram, where publisher content often struggles to compete with alternative sources such as personalities and influencers.